‘I am Chandalini, and I am Proud of that. You must Accept and Respect it’: Conversation with Kalyani Thakur Charal - CHAKRABORTY, DEBDATTA; BANERJEE, SARBANI (SARE: Southeast Asian Review of English, 2024)
This interview with the notable Bengali Dalit woman writer in the realm of Caste and Gender Studies, Kalyani Thakur Charal, encompasses the diverse facets of caste-gender centric issues, caste-based stratification, particularly in connection with the Bengali Dalit community in the context of West Bengal. She puts forward her argument on the matters of caste-gender intersectionality, the impact of patriarchy, and the marginalization of Bengali Dalit women section. This discussion sheds light on the anti-caste struggle, which was prominent in Bengal during the colonial times, the major personas related with that struggle, the experiences of the Bengali Dalit strata in West Bengal, the partition of India in 1947 and its effect on the Bengali Dalits and most importantly the challenges faced by the Bengali Dalit women strata along with the issues of their triple marginalization.